Contrasting Explicit With Implicit Measures of Children's Representations: The Case of Segmental Phonology. Issue 2 (15th January 2019) - Ainsworth, Steph; Welbourne, Stephen; Woollams, Anna; Hesketh, Anne
Abstract: Current theories of phonological development make contrasting predictions about the role of vocabulary growth and orthographic knowledge in the emergence of segmental phonological representations. Testing these predictions in children is made difficult by the metacognitive nature of tasks used to assess phonological representations. In this study, we used novel tasks to measure the sensitivity of 88 children (3 years 2 months–5 years 7 months) to phonological segments, without requiring them to have any explicit awareness of the sounds in words. We contrasted these measures with measures requiring explicit segmental analysis of word forms. Results showed that, although explicit segmental analysis is related to letter–sound knowledge, tasks measuring implicit segmental sensitivity provide evidence of segmental phonology related to vocabulary growth and not mediated by orthography. Findings highlight the importance of tapping into the structure of children's phonological representations using tasks that minimize the requirement for explicit awareness. Abstract :